Aleochara (Coprochara) bimaculata Gravenhorst 1802 - Majka, Christopher; Klimaszewski, Jan (Zenodo, 2010)
Aleochara ( Coprochara ) bimaculata Gravenhorst, 1802 NEW BRUNSWICK: Kent County: Buctouche, 13.VI.2007, 18.X.2007, J.P.- Michaud, on decomposing pig (2, UMNB). Aleochara bimaculata is newly recorded in New Brunswick. In Canada it has been previously recorded in Alberta, British Columbia, Manitoba, Newfoundland and Labrador, Nova Scotia, Northwest Territories, Ontario, Québec, and Saskatchewan. It is found throughout the United States, south to southern Mexico (Klimaszewski 1984). Adults are frequently found at dung, carrion, decomposing mushrooms, and in various kinds of leaf and grass litter (Klimaszewski 1984) : Published as part of Majka, Christopher & Klimaszewski, Jan, 2010, Contributions to the knowledge of the Aleocharinae (Coleoptera, Staphylinidae) in the Maritime Provinces of Canada, pp. 15-39 in ZooKeys 46 (46) on page 17, DOI: 10.3897/zookeys.46.413, http://zenodo.org/record/576663 : {"references": ["Klimaszewski J (1984) A revision of the genus Aleochara Gravenhorst of America north of Mexico (Coleoptera: Staphylinidae, Aleocharinae). Memoirs of the Entomological Society of Canada 129: 1 - 211."]}